DANCE IN PHYSICAL EDUCATIONTHE CONTEXT IN THE CANINDÉ-CE PUBLIC SCHOOLS (Fiep Bulletin - online, 2017)
Dance is considered one of the oldest forms of manifestation of the body. In all times and in variousgeographic spaces, dance has played for the peoples a form of representation, expression and communication of their culturalcharacteristics. By means of gestures and movements the dance translated its most intimate emotions, accompanied or not ofmusic (DARIDO, 2011). According to Nanni (2003) the human being used dance as body language, as a representation ofseveral aspects of human life. Methodology: The sample was composed by Physical Education teachers of the municipal schoolsof the city of Canindé, of both sexes, being 28 Teachers. This study was carried out in all municipal public schools in the city ofCanindé - CE, totaling 21 schools, located in this city and its districts. The present study deals with field research, descriptive andcross-sectional, using quantitative analysis resources. A quantitative approach is considered when data are eligible and seekconclusive evidence (ALVES, 1991). Results: Through this Study we verified the reasons that lead the Physical Educationteacher not to effect the dance in their classes. 43% answered that they do not dominate this area of education. Regarding thefactors influencing non-teaching of dance, 39% answered that the lack of skills and the lack of complementary training are therelevant factors for the absence of this teaching. This data points to a reflection about the commitment that the teacher shouldhave as an educator, assuming a conscious activity in the search of a pedagogical practice, aiming at a social transformation.Conclusion: The data imply the need to create mechanisms of accessibility to dance in the Classes of Physical Education, theseresults may favor the development of effective analyzes of the social segments committed to artistic making.
Keywords: Dance. Physical Education.Teaching